Book review of education and technology: Key issues and debates / Noridah Abu Bakar - Abu Bakar, Noridah (Penerbit UiTM (UiTM Press), 2017)
The book is written by Neil Selwyn, a Professor from the Faculty of Education in Monash University, Australia to probe our mind regarding issues of technology use in education that seems like inconsistent and often results in unintended consequences and subtle side-effects. The author makes an effort to highlight the problematic as well as the positive aspects of education and technology where most technology development is driven by ambitions to improve and innovate...